1989
DOI: 10.1159/000116417
|View full text |Cite
|
Sign up to set email alerts
|

Adrenoleukodystrophy Presenting as Spinocerebellar Degeneration

Abstract: The clinical features of 3 patients from a kindred with adrenoleukodystrophy and the analysis of their plasma sphingomyelin are described. Onset of symptoms was between the ages of 33 and 54 years. Ataxic gait and spasticity were the only symptoms noted during the early stage of the disorder. Dementia and optic atrophy were present in two of the cases. Baseline plasma Cortisol was normal, but adrenocorticotropic hormone was elevated. Analysis of plasma sphingomyelin demonstrated an increase in very-long-chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
(43 reference statements)
2
2
0
Order By: Relevance
“…2,4,7,22 Immunohistochemical studies have shown that MBP is not a component of GCIs. [23][24][25] The present study also showed that GCIs do not contain the anti-EP/ QD-9 epitope, corresponding to hMBP 82 to 86. The appearance of GCIs is thought to precede the other changes of neuronal loss, gliosis, and myelin pallor.…”
Section: Discussionsupporting
confidence: 63%
“…2,4,7,22 Immunohistochemical studies have shown that MBP is not a component of GCIs. [23][24][25] The present study also showed that GCIs do not contain the anti-EP/ QD-9 epitope, corresponding to hMBP 82 to 86. The appearance of GCIs is thought to precede the other changes of neuronal loss, gliosis, and myelin pallor.…”
Section: Discussionsupporting
confidence: 63%
“…To the best of our knowledge, there are reports of 17 cases of adrenoleukodystrophy presenting as spinocerebellar degeneration or olivopontocerebellar atrophy worldwide. Clinical presentations of these cases were similar to spinocerebellar ataxia or olivopontocerebellar atrophy similar to our patient 3,4,5,6,7,8,9,11,12,13,14…”
Section: Discussionsupporting
confidence: 85%
“…Childhood cerebral ALD and adrenomyeloneuropathy (AMN), the two most common phenotypes, account for 70-80% of patients with X-ALD 1,2. Presentation as spinocerebellar degeneration or olivopontocerebellar degeneration have been rarely reported in literature,3,4,5,6,7,8,9 and these reports described a mutation in exon 2 or exon 8 of the ABCD1 gene in these unusual phenotypic variants of X-ALD 4,5,9. Herein, we report a Korean male with X-ALD with an isolated lesion in the cerebellar white matter and dentate nuclei, derived from a de novo mutation in exon 1 at nucleotide position c.277_296dup20 (p.Ala100Cysfs * 10) of the ABCD1 gene.…”
Section: Introductionmentioning
confidence: 99%
“…Childhood cerebral ALD and adrenomyeloneuropathy (AMN), the two most common phenotypes, account for 70-80% of patients with X-ALD [3]. Clinical presentation as spinocerebellar ataxia has been rarely reported [4][5][6][7][8][9][10]. Only one of the very few reports has described a mutation of exon 2 of the ABCD1 gene in this unusual phenotypic variant of X-ALD [4].…”
Section: Introductionmentioning
confidence: 99%